Usefulness of CT texture analysis in differentiating benign and malignant renal tumours. Issue 2 (February 2020) - Deng, Y.; Soule, E.; Cui, E.; Samuel, A.; Shah, S.; Lall, C.; Sundaram, C.; Sandrasegaran, K.
Abstract : AIM: To elucidate visually imperceptible differences between benign and malignant renal tumours using computed tomography texture analysis (CTTA) using filtration histogram based parameters. MATERIALS AND METHODS: A retrospective study was performed by texture analysis of pretreatment contrast-enhanced CT examinations in 354 histopathologically confirmed renal cell carcinomas (RCCs) and 147 benign renal tumours. A region-of-interest was drawn encompassing the largest cross-section of the tumour on venous phase axial CT. CTTA features of entropy, kurtosis, mean positive pixel density, and skewness at different spatial filters were calculated and compared in an attempt to differentiate benign lesions from malignancy. RESULTS: Entropy with fine spatial filter was significantly higher in RCC than benign renal tumours ( p =0.022). Entropy with fine and medium filters was higher in RCC than lipid-poor angiomyolipoma ( p =0.050 and 0.052, respectively). Entropy >5.62 had high specificity of 85.7%, but low sensitivity of 31.3%, respectively, for predicting RCC. CONCLUSIONS: Differences in entropy were helpful in differentiating RCC from lipid-poor angiomyolipoma, and chromophobe RCC from oncocytoma. This technique may be useful to differentiate lesions that appear equivocal on visual assessment or alter management in poor surgical candidates. Highlights: Lipid-poor angiomyolipoma and renal cell carcinoma may share imaging features. Oncocytoma may be difficult to distinguish from chromophobe renal cell carcinoma. CT texture analysis may assist in differentiating these entities, non-invasively. Entropy was significantly increased in malignant renal tumors compared to benign.